1999
DOI: 10.1080/003655299750024706
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Gastrointestinal Symptoms in Young and Middle-Aged Diabetic Patients

Abstract: Diabetic patients had more gastrointestinal symptoms than non-diabetic population. These symptoms did not correlate with duration of the disease, metabolic control, or any other complication except neuropathy. Heartburn and constipation were among the symptoms that occurred more frequently in diabetic patients than in the non-diabetic population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
1
8

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(67 citation statements)
references
References 10 publications
4
52
1
8
Order By: Relevance
“…Research suggests that a reconstruction of inhibitory and excitatory neurons occurs in patients with diabetes, leading to a weakened muscular response in which nerve fibers are an intermediary, and which directly translates to observed gastrointestinal motility disorders. To a greater degree the damage most probably concerns inhibitory neurons, particularly nNOS (neuronal nitric oxide synthase), the number of which decreases in diabetes, as well as VIP and neuropeptide Y [18]. Reduced expression, or activity, of nNOS is probably the most consistent change in respect to ENS, although there is a research indicating an increase or no change in nNOS in patients with diabetes [13].…”
Section: Pathogenesismentioning
confidence: 99%
“…Research suggests that a reconstruction of inhibitory and excitatory neurons occurs in patients with diabetes, leading to a weakened muscular response in which nerve fibers are an intermediary, and which directly translates to observed gastrointestinal motility disorders. To a greater degree the damage most probably concerns inhibitory neurons, particularly nNOS (neuronal nitric oxide synthase), the number of which decreases in diabetes, as well as VIP and neuropeptide Y [18]. Reduced expression, or activity, of nNOS is probably the most consistent change in respect to ENS, although there is a research indicating an increase or no change in nNOS in patients with diabetes [13].…”
Section: Pathogenesismentioning
confidence: 99%
“…The Domestic/International Gastroenterology Surveillance Study demonstrated those suffering from a metabolic or endocrine disorder (which would presumably include in large part, diabetes) were 2.6-to 4.4-fold more likely to report upper gastrointestinal symptoms in the prior three months (p<0.006) [8]. A study of Swedish type II diabetics (n=61) and non-diabetics (n=106) asked to complete a gastrointestinal symptom checklist found type II diabetes were more likely to report abdominal pain more often than once a month (28.3% versus 14.3%, p<0.01) and heartburn (31.77% versus 14.0%, p<0.05) [37]. Interestingly, it appears that the prevalence of upper gastrointestinal symptoms in diabetics may be linked to the extent/ severity of their disease, with a large (n=1,101) cross-sectional survey study demonstrating higher adjusted odds of frequent abdominal pain (odds ratio=1.62, 95% confidence interval, 1.02-2.58), dysmotility-like dyspepsia (odds ratio=2.01, 95% confidence interval, 1.30-3.11), ulcer-like dyspepsia (odds ratio=1.49, 95% confidence interval, 0.90-2.45) and gastroesophageal reflux symptoms (odds ratio=2.28, 95% confidence interval, 1.54-3.38) in patients experiencing a diabetes-related complication compared to those whom did not, and higher adjusted odds of dysmotility-like dyspepsia (odds ratio=1.32, 95% confidence interval, 1.08-1.60), ulcerlike dyspepsia (odds ratio=1.36, 95% confidence interval, 1.06-1.75) in those with poorer hemoglobin A1c control [38].…”
Section: Diabetesmentioning
confidence: 99%
“…The finding of higher prevalence rates of upper gastrointestinal symptoms in patients with cardiovascular disease may exist for a number of reasons. First, there are a host of mutual risk factors for developing both cardiovascular disease and upper gastrointestinal symptoms [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. Next, patients experiencing both health problems often complain of similar or overlapping symptomatology, potentially resulting in the more frequent surveillance and diagnosis of both [38].…”
Section: Introductionmentioning
confidence: 99%
“…The frequency of gastrointestinal complications in patients with diabetes varies in different studies between 25% and 76% (9,10,15,20,23). Symptoms such as nausea and vomiting, abdominal pain, diarrhoea, constipation and faecal incontinence are common in these patients (9,10,15,20,23).…”
Section: Introductionmentioning
confidence: 99%
“…Symptoms such as nausea and vomiting, abdominal pain, diarrhoea, constipation and faecal incontinence are common in these patients (9,10,15,20,23). Gastrointestinal complications in patients with diabetes are attributed to disturbed gastrointestinal motility (1,12).…”
Section: Introductionmentioning
confidence: 99%